The Qualities of English Textbooks For The Tenth Grade Students - Diyah Trinovita (Syntax Literate, 2022)
The objective of this research is to describe the qualities of the three English textbooks. This research was conducted using content analysis. The object of this research were three English textbooks, they are Bahasa Inggris, Pathway to English, and Talk Active for the tenth grade of senior high school. This research adapted from the combination criteria between Cunningsworth and criteria of good textbook from the government (BSNP). The data were obtained through interview, and document analysis. The data were analyzed through four steps - collection, reduction, display, and conclusion. The results show that BI book fulfilled six of seven criteria of good textbook and was categorized as suitable. PE book fulfilled two of seven criteria of good textbook and was categorized as partly suitable. TA book fulfilled three of seven criteria of good textbook and was categorized as partly suitable. Bahasa Inggris written by Utami Widiati, Zuliati Rohmah, dan Faridah is suitable to be used by the teacher and tenth grade students of Senior High School because this book almost fulfilled all criteria of a good textbook based on the combination criteria between Cunningsworth and BSNP.